SYNTHESIS AND CHARACTERIZATION POLYELECTROLYTES COMPLEXES (PECs) BASED ON CHITOSAN AND POLY-2-ACRYLAMIDO-2-METHYLPROPANE SULFONIC ACID (PAMPS) IN PHYSIOLOGICAL SODIUM CHLORIDE SOLUTION - Jatmiko, Agus
Polyelectrolytes complexes (PECs) are one of material which can be used as drug carrier for drug delivery system. Particle size, morphology and surface charge of particle becoming important parameters in drug delivery system. In this study, PECs based on chitosan (CS) and Poly-2-acrylamido-2-methylpropane sulfonic acid (PAMPS) have been prepared by simple mixing method from its polymer solution. Three sample of PECs with different concentration chitosan/PAMPS (0.01/0.01 %(w/v), 0.025/0.01 %(w/v), 0.05/0.01 %(w/v)) have been prepared to observed the influence of chitosan concentration on particle size, morphology, and surface charge of PECs. Dynamic Light Scattering (DLS) result show that obtained particle size in the range 249.1 nm - 318.2 nm. Zetasizer result showed that balance from combination chitosan and PAMPS obtained on 0,025 % (w/v) chitosan concentration, with zeta value 0.06 mV. Fourier Transform Infra Red (FTIR) also confirmed that N-H from chitosan and S=O from PAMPS have been bonding each other, due to disapperance of peak from N-H bending, out of plane N-H wagging and S=O from sulfonate . However, morphology of PECs can’t be observed due to NaCl impurity which covered PECs particle. Dialysis process required to purify PECs solution from its impurities (NaCl). Addition of glutaraldehyde needed to conserve the original structure of PECs during dialisis process. After dialysis process and addition of glutaraldehyde, morphology of PECs can be observed. DLS showed that after glutaraldehyde addition, average particle size become smaller from 213.4 nm - 302.2 nm. But particle distribution after glutaraldehyde addition become broadening and large particle size occurred in this sample. Apperance of larger particle size, might be due to over-crosslinking of glutaraldehyde. This hypothesis has been confirmed from FTIR result, that excess GA appeared in peak 1720.5 cm-1. Zetasizer result showed that surface charge after addition of glutaraldehyde become more negative (-1.02 mV). This might be due to glutaraldehyde only bind with chitosan, and caused PAMPS become excessive.